2022
DOI: 10.1145/3512977
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Design Space of AI-Mediated Social Interaction in Online Learning: Challenges and Opportunities

Abstract: Our online interactions are constantly mediated through Artificial Intelligence (AI), especially our social interactions. AI-mediated social interaction is the AI-facilitated process of building and maintaining social connections between individuals through information inferred from people's online posts. With its impending application across a number of contexts, the challenges and opportunities of AI-mediated social interaction remain underexplored. This paper seeks to understand the design space of AI-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The full-text screening was conducted for the remaining 73 papers, and 15 articles were selected for inclusion in this review: conference papers (n = 4), unpublished dissertations (n = 1), and peer-reviewed journal articles (n = 10). [14][15][16]30,31,[37][38][39][40][41][42][43][44][45][46] Search outcomes are reported using the PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full-text screening was conducted for the remaining 73 papers, and 15 articles were selected for inclusion in this review: conference papers (n = 4), unpublished dissertations (n = 1), and peer-reviewed journal articles (n = 10). [14][15][16]30,31,[37][38][39][40][41][42][43][44][45][46] Search outcomes are reported using the PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…17 Programming with NLP and AI capabilities will facilitate the accuracy and effectiveness of the chatbot in communicating with users. 38,44,46 Local health care workers and intended chatbot users can help improve the chatbots' understanding of the languages and cultural norms of targeted communities. 56…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, female secondary students (𝑥̅ =2.534, SD=0.548) found virtual learning environment communication more problematic than did the males (𝑥̅ =2.263, SD=0.566). Wang et al (2022) observed that females find it tougher to communicate socially and digitally due to the various digital platforms. Young women were twice as likely to feel depression in an environment with a notable lack of in-person connection and engagement, as did young men (Davis et al, 2022).…”
Section: Perceived Level Of Challenges Faced By Students During Virtu...mentioning
confidence: 99%